Correlation between Endobutton Position and Functional Outcome After ACL Reconstruction: Plain Xray Evaluation - Mahyudin Mahyudin; Ricky Wibowo; Ghuna Arioharjo Utoyo (Berkala Kedokteran, 2020)
Abstract: The correct positioning of the femoral tunnel and endobutton position determine the success of ACL reconstruction (ACLR). Improper femoral tunnel placement most common errors in failed ACLR. However, plain post-operative imaging in the early state is not routinely performed. EndoButton position evaluation by XRay was made because this technique was cheap and reliable in Indonesia. There is no consensus on the ideal positioning of EndoButton in compare with functional outcome after ACLR.  The study aimed to evaluate anatomic positions of tunnel and fixation devices, and also provide a baseline examination for future controls regarding tunnel placement and fixation devices, and also evaluation functional outcome after ACL procedure and also evaluation of functional outcome after ACLR with IKDC score. Between February 2019 to July 2019, 20 patients aged 17 to 59 years, with post ACL reconstruction were involved in this study. We are evaluating sex, age, affected the side of the knee, complication after an operation, related activity with injury, and evaluation postoperatively with femoral angle measurement Xray AP and lateral view. We also evaluated and correlate post ACRL and functional outcomes with the International Knee Documentation Committee (IKDC) score. The mean age of patients was 28,38 ± 9,3 years, (87,15% men and 12,5% women). There is no complication after the operation in all patients. Nine patients (56,3%) affected on the left side, and seven patients (43,8%) affected right-sided. All patients are performed single-bundle augmentation techniques for ACL reconstruction. Five (31,3%) patient has history fall and eleven (68,8%) patients caused by sports activity. All patient has Femoral angle measurement from knee AP view x-rays more than 17o, with minimum 39o and maximum 54o, with mean 46,63 ± 4,2. From lateral x rays, we interpreted nine patients (45%) interpreted as shallow and high, and 55% others interpreted as deep and low (optimal). The mean of IKDC score pre-op was 58,1±4,6 and means IKDC postoperatively 6 months was 84,68 ± 5,1. There was a significant difference in functional outcome between optimal endobutton and not optimal endobutton position group with p-value < 0,05. Early post-operative imaging (knee x-rays) provides useful information regarding tunnel placement and fixation devices. It also serves as a baseline examination for future reference. In this study, a single bundle ACL reconstruction shows a satisfying outcome. Keywords: Anterior cruciate ligament; knee; postoperative reconstruction; radiograph.